Singlet Oxygen In Vivo: It Is All about Intensity-Part 2 - Hackbarth, Steffen; Gao, Shanghui; Šubr, Vladimír; Lin, Lisheng; Pohl, Jakob; Etrych, Tomáš; Fang, Jun (Journal of personalized medicine, 2023)
Recently, we reported induced anoxia as a limiting factor for photodynamic tumor therapy (PDT). This effect occurs in vivo if the amount of generated singlet oxygen that undergoes chemical reactions with cellular components exceeds the local oxygen supply. The amount of generated singlet oxygen depends mainly on photosensitizer (PS) accumulation, efficiency, and illumination intensity. With illumination intensities above a certain threshold, singlet oxygen is limited to the blood vessel and the nearest vicinity; lower intensities allow singlet oxygen generation also in tissue which is a few cell layers away from the vessels. While all experiments so far were limited to light intensities above this threshold, we report experimental results for intensities at both sides of the threshold for the first time, giving proof for the described model. Using time-resolved optical detection in NIR, we demonstrate characteristic, illumination intensity-dependent changes in signal kinetics of singlet oxygen and photosensitizer phosphorescence in vivo. The described analysis allows for better optimization and coordination of PDT drugs and treatment, as well as new diagnostic methods based on gated PS phosphorescence, for which we report a first in vivo feasibility test.
Keywords: illumination intensity; singlet oxygen; photodynamic therapy; time-resolved phosphorescence